Development of an aeration system for smart aquaculture farming - Chan, Matthew Yun Xin (2022)
Aquaculture has seen much development in recent years but is still lagging in terms of smart technology when compared to that of other agriculture sectors. However, there are certain inefficiencies in current aquaculture technology, mainly the slow reaction time to changes in water quality in traditional farms and the unnecessary wastage of resources such as electricity. The purpose of this project was to develop a smart aeration system for aquaculture farming as dissolved oxygen (DO) is one of the most crucial factors in an aquaculture environment. The aims of this project were to develop an aerator prototype, the algorithms for real-time monitoring, autonomous response, integration with an Internet of Things (IoT) cloud platform and to conduct a feasibility study on the smart aeration system for controlling the DO level within an aquaculture system. In the development of the smart aeration system, SolidWorks was used for the 3D CAD designing of the mechanical components, the Arduino IDE was used for the software development aspects and Proteus was used to design the circuit for the electrical components of the system. The main components of the smart aeration system were NodeMCU, sensors, power supply, motor and impeller. The system could connect to the Blynk IoT cloud platform to both transmit data from the sensors to be displayed on the web interface or mobile application and receive instructions from the user wirelessly. Three impeller prototypes were designed and tested to determine the characteristics of the best impeller for the application, the best impeller was capable of increasing the DO percent saturation of the test environment by 15 % over 2 hours. The smart aeration system developed successfully demonstrated the capabilities to increase the DO percent saturation of water and maintain it autonomously at a targeted value of +5 % the initial value even when fish feed was added to act as a DO remover.